An Analysis of the Usage of Probability Markers in Print Advertising of Hygiene and Cleaning Products - Putri Rindu Kinasih; Estri Cinta Tyas Gusti (Metathesis: Journal of English Language, Literature, and Teaching, 2022)
Language plays a role in the meaning of consumer products in numerous ways. As a result, while establishing an advertising campaign for any ethnic group, language and media are crucial concerns. Surprisingly, English is being increasingly widely used in print advertising in countries like Indonesia, where English is not the predominant language of communication. This study aims to find the effect of using English and the usage of probability markers in triggering purchase intentions towards hygiene and cleaning related products due to Covid-19. This study adopted the mixed-method approach. The researchers distributed questionnaire adapted from Hornikx et al. (2010) to 150 participants and interviewed 15 people. The results showed that the participants preferred English version ads. In addition, when making an advertisement, advertisers must not only choose the appropriate language, but also the appropriate diction. Then, the participants agree that pledges as probability markers influenced their decision to purchase hygiene and cleaning products. Lastly, while designing advertisements, related to hygiene and cleaning products, the advertiser should pay special attention to the body-copy (writings).